Media Exposure and Corporate Labor Investment Decisions - Baloria, Vishal P.; Lo, Alvis K.; Shu, Susan (The Accounting Review, 2025)
ABSTRACT We examine whether the media can act as a friction that hampers the efficiency of corporate labor investment, a decision that attracts significant media attention. We develop a new measure of media exposure that takes into account the circulation and geographic proximity of a comprehensive set of media outlets. We show media exposure leads to greater labor investment inefficiency. Closer examination reveals that media exposure is associated with firms underhiring, but not underfiring. This underinvestment in labor by managers helps avoid future layoffs but is inefficient in that firms are left understaffed relative to their economic fundamentals. Further, we find that managers’ concerns about their personal reputation, but not the firm’s reputation, primarily drive our results. Our findings illustrate that the media can serve as a friction for, in addition to being a facilitator or monitor of, corporate labor investment decisions. Data Availability: All data are available from public sources identified in the paper. JEL Classifications: D25; G31; M51.